Associations between the acclimation of phloem-cell wall ingrowths in minor veins and maximal photosynthesis rate - Adams, William W.; Cohu, Christopher M.; Amiard, Véronique; Demmig-Adams, Barbara (Frontiers in Plant Science, 2014)
The companion cells (CCs) and/or phloem parenchyma cells (PCs) in foliar minor veins of some species exhibit invaginations that are amplified when plants develop in high light (HL) compared to low light (LL). Leaves of plants that develop under HL also exhibit greater maximal rates of photosynthesis compared to those that develop under LL, suggesting that the increased membrane area of CCs and PCs of HL-acclimated leaves may provide for greater levels of transport proteins facilitating enhanced sugar export. Furthermore, the degree of wall invagination in PCs (Arabidopsis thaliana) or CCs (pea) of fully expanded LL-acclimated leaves increased to the same level as that present in HL-acclimated leaves seven days following transfer to HL, and maximal photosynthesis rates of transferred leaves of both species likewise increased to the same level as in HL-acclimated leaves. In contrast, transfer of Senecio vulgaris from LL to HL resulted in increased wall invagination in CCs, but not PCs, and such leaves furthermore exhibited only partial upregulation of photosynthetic capacity following LL to HL transfer. Moreover, a significant linear relationship existed between the level of cell wall ingrowths and maximal photosynthesis rates across all three species and growth light regimes. A positive linear relationship between these two parameters was also present for two ecotypes (Sweden, Italy) of the winter annual A. thaliana in response to growth at different temperatures, with significantly greater levels of PC wall ingrowths and higher rates of photosynthesis in leaves that developed at cooler versus warmer temperatures. Treatment of LL-acclimated plants with the stress hormone methyl jasmonate also resulted in increased levels of wall ingrowths in PCs of A. thaliana and S. vulgaris but not in CCs of pea and S. vulgaris. The possible role of PC wall ingrowths in sugar export versus as physical barriers to the movement of pathogens warrants further attention.